New iOS features for developers: SwiftData, SwiftUI 3.0, WidgetKit, App Intents - Vdovenko, Dmytrii; Seidykh, Olga (My University, 2025)
Apple's new tools — SwiftData, SwiftUI 3.0, WidgetKit, and App Intents — significantly expand developers' capabilities. They enable efficient data management, modern interface design, integration with system functions, and improved user interaction. Using these technologies facilitates the creation of innovative, productive, and personalised applications for the iOS ecosystem. Нові інструменти Apple — SwiftData, SwiftUI 3.0, WidgetKit і App Intents — істотно розширюють можливості розробників. Вони забезпечують ефективне керування даними, створення сучасного інтерфейсу, інтеграцію з системними функціями та покращену взаємодію з користувачем. Використання цих технологій сприяє створенню інноваційних, продуктивних і персоналізованих застосунків для екосистеми iOS.
Keywords: mobile applications; framework; iOS ecosystems; кафедра інформаційних технологій, штучного інтелекту і кібербезпеки; мобільні застосунки; фреймворк; екосистеми iOS